Lingering sex and age disparities in dolutegravir uptake among adults with HIV: a multicountry observational cohort study - Ellen Brazier; Matthew L Romo; Andrea L Ciaranello; Francesca Odhiambo; Sanjay Pujari; Gad Murenzi; Charles Kasozi; Sasisopin Kiertiburanakul; Dominique Mahambu Nsonde; Winnie Muyindike; Vohith Khol; Patricia Lelo; et al. (BMJ Global Health, 2026)
Introduction: Since July 2019, the WHO has recommended dolutegravir (DTG)- based regimens as preferred first- line antiretroviral therapy (ART) for adults and adolescents living with HIV (DTG- for- All), a reversal of a 2018 safety alert on use of DTG- based regimens by women of reproductive age (WRA). We examined sex and age disparities in DTG uptake before and after DTG- for- All in the International epidemiology Databases to Evaluate AIDS. Methods: We included patients ≥16 years on or initiating treatment between January 2017 and July 2021 in 14 low- and middle- income countries where initial guidelines on DTG- based regimens for first- line ART either restricted use by WRA or had no such restrictions. We estimated the cumulative incidence of DTG uptake (CI- DTG) by sex and age group (aged 16–49 years vs 50+ years), stratified by patient, clinic and setting characteristics. Results: Among 177 706 patients on ART during the study period, 51% were females aged 16–49 years, with 25% males aged 16–49 and 13% and 11%, respectively, females and males aged 50+. At the time of DTG- for- All, overall CI- DTG was 29.6% (95% CI 29.4% to 29.8%); it was lower among females aged 16–49 (16.2%; 95% CI 16.0% to 16.5%) than males (41.1%; 95% CI 40.6% to 41.5%), with no sex disparities among patients aged 50+ (females: 46.0%; males: 47.0%). While DTG uptake subsequently increased among all groups, by July 2021, it remained substantially lower among females 16–49 (66.4%; 95% CI 66.1% to 66.7%), compared with males 16–49 and older females and males (75.8% to 77.5%). Concentrated in countries where initial guidelines on DTG restricted use by WRA, disparities in DTG uptake persisted at all health system levels and in both low- income and lower- middle- income countries. Conclusions: While sex- age differentials in DTG uptake narrowed after WHO’s DTG- for- All recommendation, lingering disparities in uptake underscore the difficulty of policy de- implementation when new evidence emerges.
Keywords: WHO; dolutegravir (DTG; Lingering sex; Age disparities